DETERMINANTS OF ACADEMICS' JOB SATISFACTION: EXAMINING THE PERSPECTIVE OF ACADEMIC STAFF (Nonconventional Technologies Review, 2023)
The job satisfaction of academic staff is influenced by several variables with intricate functions, such as work intensity, quality of working time, working conditions, employee motivation, and career development prospects. This study aims to investigate the impact of factors contributing to enhanced job satisfaction of academic staff in Romania, with a specific focus on research, development, and innovation activities. A conceptual model of job satisfaction was developed based on the nine dimensions identified in the literature, and it was applied to the selected target group. The study utilized a convenience or availability-based sampling method, and 17 semi-structured research interviews were conducted with respondents from diverse research fields. The interview guide included questions that were focused on the dimensions studied. Analysis of the interview data revealed that three factors, namely Research recognition and value, Efficient management, and Work incentives, were significant contributors to academic staff job satisfaction. Therefore, it is recommended that academic management should concentrate on these areas of human resource management to enhance academic staff job satisfaction and employee retention. This study provides valuable insights into employee strategies and satisfaction practices that could assist university management in improving overall job satisfaction.